Chronic Wasting Disease In Cervids: Prevalence, Impact And Management Strategies - Rivera NA (Dove Medical Press, 2019)
Nelda A Rivera,1 Adam L Brandt,2 Jan E Novakofski,3 Nohra E Mateus-Pinilla1 1Illinois Natural History Survey-Prairie Research Institute, University of Illinois Urbana-Champaign, Champaign, IL, USA; 2Division of Natural Sciences, St. Norbert College, De Pere, WI, USA; 3Department of Animal Sciences, University of Illinois Urbana-Champaign, Urbana, IL, USACorrespondence: Nohra E Mateus-PinillaIllinois Natural History Survey-Prairie Research Institute, University of Illinois Urbana-Champaign, 1816 South Oak Street, Champaign, IL 61820, USATel +12173336856Fax +12172440802Email nohram@illinois.eduAbstract: Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy (TSE) that affects members of the cervidae family. The infectious agent is a misfolded isoform (PrPSC) of the host prion protein (PrPC). The replication of PrPSC initiates a cascade of developmental changes that spread from cell to cell, individual to individual, and that for some TSEs, has crossed the species barrier. CWD can be transmitted horizontally and vertically, and it is the only TSE that affects free-ranging wildlife. While other TSEs are under control and even declining, infection rates of CWD continue to grow and the disease distribution continues to expand in North America and around the world. Since the first reported case in 1967, CWD has spread infecting captive and free-ranging cervids in 26 states in the US, 3 Canadian provinces, 3 European countries and has been found in captive cervids in South Korea. CWD causes considerable ecologic, economic and sociologic impact, as this is a 100% fatal highly contagious infectious disease, with no treatment or cure available. Because some TSEs have crossed the species barrier, the zoonotic potential of CWD is a concern for human health and continues to be investigated. Here we review the characteristics of the CWD prion protein, mechanisms of transmission and the role of genetics. We discuss the characteristics that contribute to prevalence and distribution. We also discuss the impact of CWD and review the management strategies that have been used to prevent and control the spread of CWD.Keywords: CWD, prion, PRNP, PrPC, PrPSC, TSE